Managing a foreign exchange department : a manual of effective practice - Weisweiller, Rudi. (Cambridge ; Dover, N.H. : Woodhead-Faulkner, 1985)
This book is a practical guide to problems and procedures in the management of foreign exchange department. It also analyzes the role of foreign exchange department and an overview of recent changes and developments on the foreign exchange scene.
Includes index.
Includes bibliographical references
usc 17/07/18
Loans
Keywords: Foreign-exchange; Foreign exchange brokers; Foreign exchange administration